Treatment outcomes after reduction of the target volume of intensity-modulated radiotherapy following induction chemotherapy in patients with locoregionally advanced nasopharyngeal carcinoma: A prospective, multi-center, randomized clinical trial. Issue 1 (January 2018) - Yang, Hongru; Chen, Xin; Lin, Sheng; Rong, Jinfeng; Yang, Mi; Wen, Qinglian; Shang, Changling; He, Lijia; Ren, Peirong; Xu, Shan; Zhang, Jianwen; Liu, Qiaoli; et al.
Abstract: Purpose: To investigate whether reducing the target volume of intensity-modulated radiotherapy (IMRT) after induction chemotherapy (IC) improves the quality of life (QOL) in locoregionally advanced nasopharyngeal carcinoma (NPC) without decreasing the local control and survival rate. Patients and methods: A total number of 212 NPC patients staged as III–IVb were randomly assigned to group A ( n = 97) or group B ( n = 115) in this prospective clinical trial. All patients received IC followed by cisplatin concurrent with IMRT. IMRT was planned using the images of pre-IC in group A and post-IC in group B. Results: The dose received by normal tissues in group B was lower than that of group A ( P < 0.05). The recovery of the dry mouth symptoms in group B was significantly improved than group B. The quality of life (QOL) scores in group B were higher than group A. With a median follow-up of 35 months, the 1-year estimated overall survival (OS), progression-free survival (PFS), locoregional failure-free survival (LRFFS), distant metastasis-free survival (DMFS) in group A versus group B were 97.9% vs 97.3%, 90.7% vs 92, 2%, 99.0% vs 98.2%, 91.8% vs 94.8%. The 2-year OS, PFS, LRFFS, DMFS in group A versus group B were 93.7% vs 92.9%, 83.4% vs 84.3%, 96.8% vs 95.5%, 86.5% vs 89.5%. The 3-year OS, PFS, LRFFS, DMFS in group A versus group B were 82.3% vs 87%, 74.7% vs 83.4%, 91.8 vs 93.9%, 81.3% vs 88.6%, respectively. Conclusion: Reducing the IMRT target volume after IC did not reduce the local control and survival rate in locoregionally advanced NPC but the doses received by normal tissues were decreased, and the QOL scores were improved.